The Effect of Servant Leadership on Lecturer Performance Through Trust in Leader as A Mediation Variable - Keradjaan, Herson; Sondakh, Jullie Jeannete; Tawaas, Hendra Novie; Sumarauw, Jacky SB (Universitas Pendidikan Ganesha, 2020)
This study aimed to analyze the significant influence of Servant Leadership, Trust In leader on Performance. This research was conducted with a quantitative method through a survey approach of respondents who were permanent lecturers at the Poli Padamara Halmahera Utara through the distribution of online questionnaires (Google form). The data collected was then analyzed using the SMART PLS software. The research findings show that there is an influence of servant leadership on performance and the influence of servant leadership on trust in leaders. The results also showed the influence of trust in leader on performance and the influence of servant leadership on performance through trust in leader as a mediating variable. For further research, it is expected that further analysis of second line leaders is needed so that the results of the analysis are more comprehensive and not solely on top leadersÂ